Respiratory electron transport activity in plankton of the Weddell and Scotia Seas during late spring - early summer: relationships with other biological parameters - Estrada, Marta; Martinez, Rosa; Mathot, Sylvie (1992)
As a means to estimate potential oxygen consumption, profiles of elctron transport system (ETS) activity were made along three transects across the Weddell-Scotia Confluence zone (WSC) and the marginal ice zone (which overlapped in part) during the EPOS leg 2 cruise of the RV Polarstern. The integrated ETS activity between 0 and 100 m depth (referred to in situ temperatures) ranged from 261 meq (mili-electron equivalents) m -2 day -1 in the WSC to 45 meq m -2 day -1 in the southernmost stations at 62° S. The temporal changes in the overall distribution of ETS activity were small compared with the spatial variations. The main feature of the ETS activity distribution was the presence of maxima located in the WSC, coinciding with peaks of phytoplankton biomass. Different relationships between ETS and chlorophyll a concentration in these maxima appeared to be related to diatom or flagellate dominance. Vertically integrated ETS activities were significantly correlated with chlorophyll a and paniculate organic carbon concentrations, primary production and bacterial thymidine uptake. © 1992 Springer-Verlag. SCOPUS: ar.j info:eu-repo/semantics/published